Methylparaben stimulates tumor initiating cells in ER+ breast cancer models. Issue 4 (1st September 2016) - Lillo, M. Angeles; Nichols, Cydney; Perry, Chanel; Runke, Stephanie; Krutilina, Raisa; Seagroves, Tiffany N.; Miranda‐Carboni, Gustavo A.; Krum, Susan A.
Abstract: A body of epidemiological evidence implicates exposure to endocrine disrupting chemicals (EDCs) with increased susceptibility to breast cancer. To evaluate the physiological effects of a suspected EDC in vivo, we exposed MCF‐7 breast cancer cells and a patient‐derived xenograft (PDX, estrogen receptor positive) to physiological levels of methylparaben (mePB), which is commonly used in personal care products as a preservative. mePB pellets (4.4 μg per day) led to increased tumor size of MCF‐7 xenografts and ER + PDX tumors. mePB has been thought to be a xenoestrogen; however, in vitro exposure of 10 nM mePB failed to increase MCF‐7 cell proliferation or induction of canonical estrogen‐responsive genes ( pS2 and progesterone receptor), in contrast to 17β‐estradiol (E2) treatment. MCF‐7 and PDX‐derived mammospheres exhibited increased size and up‐regulation of canonical stem cell markers ALDH1, NANOG, OCT4 and SOX2 when exposed to mePB; these effects were not observed for MDA‐MB‐231 (ER − ) mammospheres. As tumor‐initiating cells (TICs) are also believed to be responsible for chemoresistance, mammospheres were treated with either tamoxifen or the pure anti‐estrogen fulvestrant in the presence of mePB. Blocking the estrogenic response was not sufficient to block NANOG expression in mammospheres, pointing to a non‐classic estrogen response or an ER‐independent mechanism of mePB promotion of mammosphere activity. Overall, these results suggest that mePB increases breast cancer tumor proliferation through enhanced TIC activity, in part via regulation of NANOG, and that mePB may play a direct role in chemoresistance by modulating stem cell activity. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Methylparaben (mePB) is a common preservative in personal care products and food, and is thought to be a xenoestrogen. Herein, we demonstrate that mePB led to an increased tumor size of MCF‐7 xenografts and ER + PDX tumors in nude mice. Furthermore, mePB induces the size of mammospheres and induces the transcription of stem cell markers, including NANOG.